Implementation of Performance Allowance Policy in Improving Performance of Employees, Ministry of Religion, Gorontalo Regency - Frista Iin Wahyuni (Journal of Economic, Business, and Administration (JEBA), 2020)
This study aims to: 1) Knowing and describing the implementation of the policy of providing Performance Allowances in improving employee performance at the Ministry of Religion of Gorontalo Regency, 2) Knowing and describing the factors that influence the implementation of the policy of providing Performance Allowances in improving employee performance at the Ministry of Religion of Gorontalo Regency. This study uses a qualitative method. The informants of this research are employees of the Ministry of Religion of Gorontalo Regency. This research is also a type of qualitative descriptive research because this approach is more sensitive in capturing various information phenomena. The results of the study show that: 1) The implementation of the policy of providing Performance Allowances is not in accordance with the Regulation of the Minister of Religion No. 11 of 2019 concerning the Provision of Employee Performance Allowances at the Ministry of Religion. a) the aspect of employee attendance still needs to be improved because the level of absenteeism and tardiness of employees is still too high, b) aspects of the main and functional duties still need to be reviewed because it creates social jealousy for employees who are not included in structural positions, c) aspects of the length of work still need improvements because it is not in accordance with the workload of employees, d) aspects of the quality of work produced by employees still need to be improved, because many employees do not have accuracy in their work, 2) Factors that influence the provision of Regional Performance Allowances include: work performance, expertise work and leadership